Antibacterial Performance of Biodegradable Polymer and Hazelnut Husk Flour Antibacterial Biofilm with Silver Nanoparticles - Ayrilmis, Nadir; Yurttas, Elif; Tetik, Nurten; Ozdemir, Ferhat; Palanisamy, Sivasubramanian; Alagarsamy, Aravindhan; Ramasamy, Siva; Sillanpaa, Mika; Al-Farraj, Saleh (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2024)
The antibacterial performance of biocomposite films prepared from lignocellulosic waste (hazelnut husk or hazelnut leafy green cover) modified with silver nanoparticles and polylactic acid (PLA) was determined. The amount of hazelnut husk in the PLA matrix ranged from 10 to 40% by weight in 10% increments. The composite pellets were produced using a twin-screw extruder. Biocomposite films of 0.6 mm x 40 mm x 200 mm were produced from the pellets in a laboratory hydraulic hot press. The surfaces of the modified hazelnut husk and biocomposite specimens were analyzed by scanning electron microscopy (SEM) and inductively coupled plasma optical emission spectrometry (ICP-OES). The antibacterial activity of the biocomposite films against Staphylococcus aureus bacteria was determined using the ASTM E 2149 (2020) method. The antibacterial activity of the biocomposite films increased noticeably with the addition of hazelnut husk modified with the silver nanoparticles. Compared to the pure PLA film, the biocomposite films with 10 wt% modified husk flour showed the lowest antibacterial activity (31.3%) against S. aureus over 24-h while the films with 40 wt% showed the highest antibacterial activity (99.9%). The biocomposite films made of hazelnut husk flour with silver nanoparticles and PLA matrix could be considered for food packaging applications.
Keywords: Hazelnut husk waste; Silver nanoparticles; Lignocellulosic; Antibacterial performance; Biocomposite film; CORYLUS-AVELLANA L.; ANTIOXIDANT; CELLULOSE; IONS; Materials Science